1996
DOI: 10.1182/blood.v88.8.2898.bloodjournal8882898
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vitamin D binding protein-macrophage activating factor and colony-stimulating factor-1 on hematopoietic cells in normal and osteopetrotic rats

Abstract: Osteopetrosis is a heterogeneous group of bone disorders characterized by the failure of osteoclasts to resorb bone and by several immunological defects including macrophage dysfunction. Two compounds, colony-stimulating factor-1 (CSF-1) and vitamin D-binding protein-macrophage activating factor (DBP-MAF) were used in the present study to evaluate their effects on the peritoneal population of cells and on cells within the bone marrow microenvironment in normal and incisors absent (ia) osteopetrotic rats. Previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…(15) In vitro studies have suggested that DBP may also mediate differentiation of hematopoietic cells and generate osteoclasts directly. (14,16,17) In view of these features, we considered the DBP gene to be a highly likely candidate for involvement in susceptibility to osteoporosis. In the work reported here, we examined the potential involvement of the DBP gene in the pathogenesis of osteoporosis by investigating genetic variations, constructing haplotypes, analyzing linkage disequilibrium among the variations, and carrying out multiple regression analyses to examine possible associations with BMD in 384 adult women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(15) In vitro studies have suggested that DBP may also mediate differentiation of hematopoietic cells and generate osteoclasts directly. (14,16,17) In view of these features, we considered the DBP gene to be a highly likely candidate for involvement in susceptibility to osteoporosis. In the work reported here, we examined the potential involvement of the DBP gene in the pathogenesis of osteoporosis by investigating genetic variations, constructing haplotypes, analyzing linkage disequilibrium among the variations, and carrying out multiple regression analyses to examine possible associations with BMD in 384 adult women.…”
Section: Introductionmentioning
confidence: 99%
“…This receptor takes up DBP‐bound vitamin D in urine for reabsorption into epithelial cells in proximal renal tubules (15) . In vitro studies have suggested that DBP may also mediate differentiation of hematopoietic cells and generate osteoclasts directly (14,16,17) . In view of these features, we considered the DBP gene to be a highly likely candidate for involvement in susceptibility to osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…LCA is an interesting pharmacological compound due to its antibacterial, antifungal activities, and inhibition of α-2,3-sialyltransferase [19][20][21][22][23]. The pharmacological interest in lithocholic acid is associated with the effective induction of vitamin D receptor (VDR) expression [24] and the demonstration of anticancer activity [25,26].…”
Section: Introductionmentioning
confidence: 99%